Photodynamic therapy vs. photochemical internalization: the surgical margin - Jerjes, Waseem (BioMed Central, 2011)
Controlling tumour margins in head and neck surgery is of the utmost importance in preventing loco-regional spread and distant metastasis, which will ultimately lead to a significant reduction in morbidity and mortality. We comment on the surgical margins in photodynamic therapy and photochemical internalization.